Synthesis of 2,3-Disubstituted-4(3H)-quinazolinones Using HY-Zeolite as Reusable Catalyst Under Microwave Irradiation - Montazeri, Naser; Pourshamsian, Khalil; Fomani, Arsalan; Jafar Kalantarian, Seyd (Asian Journal of Chemistry, 2012)
A new heterogeneous catalytic method to synthesize to various 4(3H)-quinazolinone derevatives, using an inexpensive and eco-friendly attractive solid catalyst, zeolite, under solvent-free and microwave irradiation conditions is described. The catalyst activity results suggest that the methodology adopted offers several advantages such as mild reaction conditions, low loading of catalyst, good yields, short reaction time and operational simplicity.